AN ANALYSIS OF ENGLISH DEIXIS USED IN “ LIGHT SWITCH” SONG LYRIC BY CHARLIE PUTH - Budik Kusworo (Universitas Al-Qolam Malang, 2025)
This research investigates the use of English deixis in the lyrics of